Pakistani Teachers’ view About Their Undergraduates’ Willingness to Communicate in English Inside the Classroom - Ubaid, Ullah; Joseph, Ramanair; Soubakeavathi, Rethinasamy; irfan, Bashir (UPM, 2022)
The main goal of modern second language (L2) pedagogy is to engender effective communication among its learners. Willingness to Communicate (WTC) has emerged as the most vibrant topic in L2 pedagogy, especially in the last two decades. A plethora of research on students’ views about their WTC has been conducted in a variety of contexts. However, research on teachers’ views about their students’ WTC in English is still in its infancy. Thus, this study investigated ESL teachers’ views about their undergraduates’ WTC in English inside the classroom. The cluster sampling technique was used to collect data from 80 ESL teachers from eight universities in Khyber Pakhtunkhwa province of Pakistan. The results revealed that the teachers viewed the undergraduates’ level of WTC as high in most classroom situations, such as during groups, during activities with the same and opposite gender, when given preparation time, seated in the middle of the class, and in front of the whole class. However, students showed a moderate level of WTC in situations such as sitting in front of the class and at the back of the class. A one-way ANOVA was performed to examine the differences between different classroom situations. The results showed significant differences in the teachers’ views about their students’ WTC in most classroom situations. Thus, the current study affirms that WTC is a dynamic variable that changes from situation to situation.